Pembelajaran Berdiferensiasi Berbantuan LKPD Bermuatan STEM pada Materi Energi Alternatif untuk Meningkatkan Keterampilan Proses Sains dan Creative Problem Solving - Sulistiani; Agus Suyatna; Undang Rosidin (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to develop a differentiated learning program assisted by student worksheets containing STEM on Alternative Energy material to improve Science Process Skills and Creative Problem Solving. The method used is research design and development using the ADDIE model stages which consist of five stages, namely analysis, design, development, implementation and evaluation. The instruments used were needs analysis questionnaires, program validation, CPS tests. Data sources for program analysis and design are students and Physics teachers from high schools in Lampung Province. Validators are experts and practitioners of physics education. Questionnaire data were analyzed using percentage techniques. CPS test results data were analyzed statistically using paired sample t-test and one way anova. The results of the research show that a high school physics learning program is needed in schools that can accommodate the different needs of students which include students' initial abilities and learning styles. The product developed, namely a differentiated learning program in the form of teaching modules and student worksheets containing STEM on Alternative Energy material, is valid and effective in increasing CPS. Differentiated learning programs include differentiation of content, processes, products. The learning process and teaching materials are adapted to students' learning styles. Students' learning readiness is accommodated by intensifying student assistance in groups.